Multisource Data Integration For Groundwater Prospecting In Precambrian Shear Zones, Espírito Santo State (Southeastern Brazil) - Hartwig, Marcos Eduardo; Moreira, César Augusto [UNESP]; de Melo, Marilane Gonzaga [UNESP] (My University, 2021)
The Precambrian metamorphic rocks in the southern region of the Espírito Santo State (southeastern Brazil) is intercepted by ductile and brittle/ductile shear zones over which towns like Guaçuí, Marechal Floriano and Domingos Martins were established. In the years of 2014 to 2016 the Espírito Santo State faced the worst drought in the past 80 years. In situations like that, the only source of fresh water available is underground. Therefore, the purpose of this study was to integrate multisource data for groundwater prospecting and management. The study area comprises the central sectors of the Guaçuí and Batatal shear zones. Methodology involved the interpretation of stereo-pairs for the identification of lineaments, electrical resistivity surveys and geological fieldwork. The results were tentatively validated with available groundwater well production data. Six resistivity profiles with a total length of 2,400 m were surveyed and 15 outcrops were described across these structures. Results have shown that the structural framework of the shear zones is predominantly made of NW to NNW and NE to NNE-trending lineaments. The former is related to brittle tectonics and the latter coincides with the ductile Precambrian fabric of the crystalline basement rocks. A near-surface porous aquifer regarded to the regolith and recent unconsolidated sedimentary deposits presenting resistivity values <1,372 Ohm.m and depths< 30 m have good potential for groundwater storage. However, results are not conclusive about the hydrogeological significance of tectonic structures for groundwater prospection in the study area.
Keywords: electrical resistivity tomography; fractured rock mass; groundwater resources; porous aquifer; structural lineaments